Stability of iron in rice noodles (Bijon) - Zulueta, Nanette V. (2000)
The use of ferrous fumarate (FF) and ferrous succinate (FS) as iron sources and rice noodles as a potential vehicle for iron fortification were investigated in this study. Rice flour from PSBRc10 rice variety was treated with FF and FS at the rates of 0, 10, 20, and 30 mg/100 g mixture of rice flour and fortificant. The physicochemical properties of the resulting mixture analyzed included color, moisture content (MC), water activity (Aw), bulk density (BD), pasting characteristics, and total iron content. The iron fortified rice flours were manufactured into rice noodles and the total retention was monitored during processing. The cooking and sensory qualities of the rice noodles were likewise determined and the available iron was assayed using in vitro technique. The storage life of the non-fortified and iron fortified products were estimated based on the half value period as calculated using the changes in microbial and cooking qualities and iron retention during storage up to a period of 28 d at 40°C and 80% relative humidity (RH). In general, MC, Aw, and BD were not affected with the addition of either FF of FS, but Kett whiteness decreased with increase rates of FF and FS (p<0.05). Addition of FF slightly decreased the breakdown viscosity but reduced the setback while an increase in FS concentration decreased the peak and final viscosities of the rice flour. Enrichment with FF or FS did not cause any significant effect on the cooking qualities of the rice noodles. Sensory qualities of the rice noodles likewise were not generally not affected up to fortification levels of 20 mg/100 g but deteriorated significantly at levels of 30 mg/100 g. A gradual increase in MC and AW were observed during storage and these were accompanied with a steady increase in the total plate count. The mold and yeast growth however, remained at a constant rate of <10 cfu/g up to the end of the 28 d storage period. The iron fortified rice noodles were estimated to be shelf stable for approximately 8 month when stored in nylon polyethylene plastic bag.